2018
DOI: 10.1007/s00497-018-0339-0
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene production and signaling in tomato (Solanum lycopersicum) pollen grains is responsive to heat stress conditions

Abstract: Tomato pollen grains have the capacity for ethylene production, possessing specific components of the ethylene-biosynthesis and -signaling pathways, being affected/responsive to high-temperature conditions. Exposure of plants to heat stress (HS) conditions reduces crop yield and quality, mainly due to sensitivity of pollen grains. Recently, it was demonstrated that ethylene, a gaseous plant hormone, plays a significant role in tomato pollen heat-tolerance. It is not clear, however, whether, or to what extent, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 59 publications
0
18
0
Order By: Relevance
“…It is noteworthy that proteins involved in the regulation of protein synthesis, in oxidative stress or in detoxification displayed a profile differing from that of the corresponding transcript ( Gallardo et al, 2007 ). In addition, ethylene-related proteins (ethylene-biosynthesis, -perception, or -signaling) were not detected in either of the pollen samples used in this study, while expression of the respective genes at transcript level was recently demonstrated by us in tomato pollen ( Jegadeesan et al, 2018 ). This may be due to low abundance of the proteins in pollen.…”
Section: Resultsmentioning
confidence: 53%
“…It is noteworthy that proteins involved in the regulation of protein synthesis, in oxidative stress or in detoxification displayed a profile differing from that of the corresponding transcript ( Gallardo et al, 2007 ). In addition, ethylene-related proteins (ethylene-biosynthesis, -perception, or -signaling) were not detected in either of the pollen samples used in this study, while expression of the respective genes at transcript level was recently demonstrated by us in tomato pollen ( Jegadeesan et al, 2018 ). This may be due to low abundance of the proteins in pollen.…”
Section: Resultsmentioning
confidence: 53%
“…AtERS2 gene shows a similar expression pattern to the ethylene receptor gene Os-ERS1 in rice that is up-regulated during early pollen development, corresponding to meiotic and microspore stages [22]. In tomato, the ethylene production capacity of pollen grains is consistent with the expression of ethylene biosynthesis and signaling genes in these tissues [23]. Moreover, the application of high concentration of exogenous ethylene on male gametophyte induces the degradation of the generative cell at meiosis stage resulting in male sterility [24].…”
Section: Male Reproductive Organsmentioning
confidence: 69%
“…In petunia, the level of ACC increases 100 fold in mature pollen grain and in anthers one day before anthesis [46]. In tomato, it was shown that pollen grain has the capacity to produce and sense ethylene before germination, as suggested by the expression of several ethylene biosynthesis and signaling genes including SlAC S3, SlAC S11, SlETR3 and SlC TR2 [23]. Nevertheless, exogenous application of ACC in flowers cannot induce the post-pollination development [47].…”
Section: Pollen Germination and Tube Growthmentioning
confidence: 99%
“…However, the phenotypic analyses performed on the 10 landraces allowed us to identify those that exhibited the best stable performances in terms of yield under a wide range of conditions, including high temperatures. Usually, heat tolerance has been evaluated under fixed climatic conditions in greenhouses or growth chambers [ 25 , 26 , 27 ]. However, these conditions do not reflect those observed in the fields during the tomato growing seasons.…”
Section: Discussionmentioning
confidence: 99%